The Application of Nanotechnology in the Codelivery of Active Constituents of Plants and Chemotherapeutics for Overcoming Physiological Barriers during Antitumor Treatment - Li, Qiushuang (Biomed Res Int, 2019)
Antitumor therapy using a combination of drugs has shown increased clinical efficacy. Active constituents derived from plants can offer several advantages, such as high efficiacy, low toxicity, extensive effects, and multiple targets. At present, the combination of plants' active constituents and chemotherapeutic drugs has attracted increased attention. Nanodrug delivery systems (NDDSs) have been widely used in tumor-targeted therapy because of their efficacy of delivering antitumor drugs. The in vivo process of tumor-targeted NDDSs has several steps. They include blood circulation, tumor accumulation and penetration, target cell internalization and uptake, and drug release and drug response. In each step, NDDSs encounter multiple barriers that prevent their effective delivery to target sites. Studies have been performed to find alternative strategies to overcome these barriers. We reviewed the recent progress of codelivery of active constituents of plants and chemotherapeutics using NDDSs. Progress into transversing the physiological barriers for more effective in vivo antitumor delivery will be discussed in this review.